Reports of Judgments, Advisory Opinions and Orders 2020: Armed Activities on the Territory of the Congo (Democratic Republic of the Congo v. Uganda) - International Court of Justice (United Nations, 2022)
Order on the decision to obtain an expert opinion in the case.